Molecular and physiological responses to water deficit in wheat (Triticum aestivum L.) (Semiárida, 2020)
Physiological and molecular responses of five wheat genotypes: one Canadian cultivar, with low temperature tolerance, and 4 experimental lines, which demonstrated in the field high yield under drought stress were studied under water stress. We determined leaf relative water content and gene expression of rob 5 and dehydrins in response to low water availability. One genotype showed a higher RWC with less leaf Iresh weight and water soil content. There were not differences between genotypes in expression genes but, we found differences in gene expression between both tested genes. Rob 5 expressed in control as well as in stressed plants, while dehydrins only expressed in stressed plants and its expression increased as the water content of leaves decreased.
Keywords: water stress; Rob 5; dehydrin; Triticum aestivum L.